Stock Market: A Comparative Study between S (Global Journal of Management and Business Research, 2013)
A healthy financial sector is crucial for economic growth. The stock market to an economy, what a clinical thermometer is to a human body, reflects the health of the economy. Again, the economy of the developed countries always has a great impact on the other economically weak countries. In this study our aim is to compare S
Keywords: S; DSE general index and volatility